Darboux Integrals for Schrödinger Planar Vector Fields via Darboux Transformations - Acosta-Humánez, P.B.; Pantazi, C. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
In this paper we study the Darboux transformations of planar vector fields of Schrödinger type. Using the isogaloisian property of Darboux transformation we prove the ''invariance'' of the objects of the ''Darboux theory of integrability''. In particular, we also show how the shape invariance property of the potential is important in order to preserve the structure of the transformed vector field. Finally, as illustration of these results, some examples of planar vector fields coming from supersymmetric quantum mechanics are studied.